Beyond the group: how food, mates, and group size influence intergroup encounters in wild bonobos. (7th January 2020) - Lucchesi, Stefano; Cheng, Leveda; Janmaat, Karline; Mundry, Roger; Pisor, Anne; Surbeck, Martin
Abstract: In social-living animals, interactions between groups are frequently agonistic, but they can also be tolerant and even cooperative. Intergroup tolerance and cooperation are regarded as a crucial step in the formation of highly structured multilevel societies. Behavioral ecological theory suggests that intergroup tolerance and cooperation can emerge either when the costs of hostility outweigh the benefits of exclusive resource access or when both groups gain fitness benefits through their interactions. However, the factors promoting intergroup tolerance are still unclear due to the paucity of data on intergroup interactions in tolerant species. Here, we examine how social and ecological factors affect the onset and termination of intercommunity encounters in two neighboring communities of wild bonobos, a species exhibiting flexible patterns of intergroup interactions, at Kokolopori Bonobo Reserve, Democratic Republic of the Congo. We recorded the timing and location of intercommunity encounters and measured fruit abundance and distribution, groups' social characteristics, and space-use dynamics over a 19-month period. We found that intercommunity tolerance was facilitated by a decrease in feeding competition, with high fruit abundance increasing the likelihood of communities to encounter, and high clumpiness of fruit patches increasing the probability to terminate encounters likely due to increased contest. In addition, the possibility for extra-community mating, as well as the potential benefits of more efficient foraging in less familiar areas, reduced the probability that the communities terminated encounters. By investigating the factors involved in shaping relationships across groups, this study contributes to our understanding of how animal sociality can extend beyond the group level. Abstract : Neighboring bonobo groups encounter each other more often when high abundance of fruits reduces feeding competition between them. When additional benefits, such as extra-group mating opportunities and potential improved foraging in less familiar areas emerge, even long-lasting intergroup associations can develop. By extending tolerant interactions beyond the group level, mechanisms such as those we describe in bonobos can lay the basis for the formation of complexly structured multilevel societies in animals.